Conversion of Levulinate Ester and Formic Acid into γ-Valerolactone Using a Homogeneous Iron Catalyst - Fu, Ming-Chen; Shang, Rui; Huang, Zheng; Fu, Yao (Synlett, 2014)
An iron-catalyzed hydrogenation of biomass-derived ethyl levulinate (EL) to γ-valerolactone (GVL) has been developed using formic acid as hydrogen source. Ethyl levulinate was converted into γ-valerolactone quantitatively under optimized reaction conditions. This catalytic process does not require the use of any base or additives.
Keywords: biomass conversion; iron catalysis; formic acid; γ-valerolactone; levulinate ester